Pengaruh Kualitas Aplikasi Terhadap Keputusan Menggunakan Jasa Transportasi Online Maxim: Survei pada Mahasiswa UNSIKA - Salma Nurhasanah; Rizka Dwi Syaharani; Abdul Yusuf (Economic Reviews Journal, 2024)
This research aims to find out how much influence application quality has on the decision to use Maxim's online transportation services with the application quality variable as the independent variable and the decision to use as the dependent variable. This study uses a quantitative approach. This research was conducted on Unsika students and the number of respondents to this research was 100 customers who had ordered Maxim online transportation services. The data collection tool uses a questionnaire and the data processing analysis tool uses SmartPLS 3.0. The results of the research state that the quality of the application has a significant influence on the decision to use Maxim's online transportation services.